Programa pró-letramento em matemática: reflexões sobre concepções, crenças e a prática de resolução de problemas de uma professora - Ricci, Sandra Regina (2013)
This work had the objective to reflect on the beliefs and concepts, as well the pedagogical practices, of the ruler teacher of 3rd year B Elementary School in 2011, at the Municipal School “Caraíbas”. This teacher was a participant in the Pro-Literacy Mathematics Program, proposed by MEC (Ministry of Education), as the continuing formation of teachers who was working with the first series, at the period of 2008/2009. We seek to question and reflect about the changes in the pedagogical action and the difficulties encountered by the teacher when trying to implement the innovations proposed by the program, in order to improve the practice in the classroom. This reflection lead to the main question: How are manifested, in the teacher’s conceptions and beliefs, the practice of solving problems that is the base of the Pro-Literacy course? To answer this question, we conducted a qualitative research, a case study, with observations on the spot, films of the Math classes, as well as an interview with the teacher. The obtained results have provided us with data, that when analyzed, enables us to realize that the teacher, subject of this research, used rather than what was proposed by the Pro-Literacy Program, and also, on her own way, appropriated the methodology of solving problems in her practice room class. That said, we realize that the concepts and practice of the teacher were just a little changed after participating in the continuing formation course, course that last six to eight months in an intense dynamic and high workload, as usually occurs with many practicing teachers in public schools.